2016
DOI: 10.1007/s10854-016-4692-1
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis and electrochemical performances of secondary carbon-coated LiFePO4-C composite for Li-ion capacitors based on neutral aqueous electrolytes

Abstract: In order to obtain LiFePO 4 (LFP) with the fine particle size and high electronic conductivity, the secondary carbon-coated LFP-C composite was synthesized by a facile two-step method with polyethylene glycol (PEG) as a grain growth inhibitor and sucrose as a main carbon source. For comparison, commercial LFP and LFP prepared without PEG and sucrose were also studied. Liion capacitors (LICs) using environmentally friendly, safe and low-cost LiNO 3 aqueous electrolyte were assembled with LFP samples as the posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…The active groups absorbed Pd atoms via chelation, which reduces the electron density around Pd atoms. The chemisorbed Pd atoms used as the catalyst for the electroless plating tabulate the chemical reaction process as follows 11 : Changes in the color of plated samples can mean electroless nickel plating on the surface of sheets. It was indicated that nickel particles deposited on the surfaces of sheets when the activated time was 1 min, and increasing the activated time would facilitate the enhance of the deposited quantity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The active groups absorbed Pd atoms via chelation, which reduces the electron density around Pd atoms. The chemisorbed Pd atoms used as the catalyst for the electroless plating tabulate the chemical reaction process as follows 11 : Changes in the color of plated samples can mean electroless nickel plating on the surface of sheets. It was indicated that nickel particles deposited on the surfaces of sheets when the activated time was 1 min, and increasing the activated time would facilitate the enhance of the deposited quantity.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the bath pH not only changed the reactivity of the bath, but also had a strong impact on microstructure and electrochemical properties of coatings. Qiu et al 11 found that the bath pH had a substantial in°uence on structural properties of plated PET substrate by printing prime in combination with palladium activation. Sun et al 12 found that the deposition rate of coating were enhanced with the increase of bath temperature.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Fig. 5(a), the Nyquist plots are composed of the semicircle in the high-frequency region, which is associated to the charge transfer resistance of electrons and electrolyte ions (R ct ), 12 and the straight line in the low frequency region, which is associated to the mass transfer or diffusion of electrolyte ions (so-called Warburg diffusion). At very high frequency, the intercept at x-axis represents the bulk solution resistance (R s ).…”
Section: Ac Impedance Analysismentioning
confidence: 99%
“…LICs are assembled with two different types of electrodes: one is an EDLC electrode (typically activated carbon) and the other one is a LIB-type electrode (such as Li 4 Ti 5 O 12 or LiFePO 4 ). 11,12 Because the LIB electrode materials possess high specic capacity, LICs can receive signicantly enhanced energy density compared to regular EDLCs. 13 Because in LIBs graphite anode is a ratelimiting electrode and at the same time Li-ion diffusion rate and electronic conductivity of the Li-ion compound cathode are relatively low, LICs with the EDLC material as one electrode and modied Li-ion compound with high electronic conductivity and Li-ion diffusion rate as the other electrode are expected to display higher power density than LIBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation